2009
DOI: 10.1091/mbc.e08-03-0313
|View full text |Cite
|
Sign up to set email alerts
|

Pil1 Controls Eisosome Biogenesis

Abstract: The molecular composition of plasma membranes is constantly remodeled by endocytosis and exocytosis. Eisosomes are large cytoplasmic protein assemblies that localize to specialized domains on the yeast plasma membrane. They are of uniform size and immobile, and their disruption leads to large aberrant plasma membrane invaginations and endocytic defects. It is unknown how eisosomes are formed or inherited and what governs their size, distribution, and location. Here we show that eisosomes are formed de novo in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 24 publications
4
89
1
Order By: Relevance
“…Similarly to the MCC patches (Moreira et al, 2009), furrow-like invaginations also seem to be randomly distributed in the membrane (Moor and Mühlethaller, 1963;Gross et al, 1978) and are most abundant in old mother cells (Takeo, 1984). In accordance with the MCC appearance on buds (Grossmann et al, 2008), few invaginations were found on dynamically developing membranes, such as young buds of S. cerevisiae and the central division ring in S. pombe (Takeo, 1984) or the germ tube of C. albicans (Miragall et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the MCC patches (Moreira et al, 2009), furrow-like invaginations also seem to be randomly distributed in the membrane (Moor and Mühlethaller, 1963;Gross et al, 1978) and are most abundant in old mother cells (Takeo, 1984). In accordance with the MCC appearance on buds (Grossmann et al, 2008), few invaginations were found on dynamically developing membranes, such as young buds of S. cerevisiae and the central division ring in S. pombe (Takeo, 1984) or the germ tube of C. albicans (Miragall et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…We assumed invaginations of a uniform length of 250 nm to be marked by a specific fluorescent marker and spread randomly (Moreira et al, 2009) on a plane ( Fig. 3A) with an overall density corresponding to the value measured on freeze-fractured cells (2.5 invaginations per μm 2 , see above).…”
Section: Surface Density Of Furrow-like Invaginations Corresponds To mentioning
confidence: 99%
“…Screening all the non-lethal single deletion mutants of yeast showed that the lipid composition of the plasma membrane had distinct effects on Transiently, this step can be observed at the tip of growing buds, as the eisosome formation beneath the newly synthesized membrane raises in the polar manner from the bud neck [20]. Upon Pil1 binding, flat, elongated areas (red) containing Sur7-like proteins, but devoid of transporters (yellow) are formed in the membrane (B).…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…Eisosome-like invaginations are found in a wide range of fungal and algal cells despite divergent molecular components (Lee et al, 2015), suggesting that eisosome function might be intricately linked to this topology. The primary component of yeast eisosomes is the BAR domain protein Pil1, which directly binds lipids at the membrane to generate invaginations (Kabeche et al, 2011(Kabeche et al, , 2014Karotki et al, 2011;Moreira et al, 2009;Olivera-Couto et al, 2011;Stradalova et al, 2009;Ziółkowska et al, 2011). Recent studies have linked eisosome function with the control of signaling pathways (Berchtold et al, 2012;Frohlich et al, 2014;Kabeche et al, 2014), but we noted that their architecture possesses the capacity to act as a membrane reservoir.…”
Section: Introductionmentioning
confidence: 99%